A virtual prototyping framework to facilitate fluid power systems realisation. Issue 2 (18th July 2008) - Fok, S.C.
The cumbersome tasks of finding suitable commercial hydraulic components and determining the static and dynamic characteristics of the system resulting from the assembly of these parts can often slow down the realisation of fluid power systems. This paper presents the framework and an internet-enabled virtual prototyping workbench to facilitate the acceleration of these systems development. The workbench can assist the designer to search for appropriate components from different suppliers, retrieve electronic data of needed components from vendors, generate virtual components from the retrieved data, assemble the virtual components, and analyse the layout, cost, weight, dimensions, assemblability as well as dynamic performances of the resulting system. These facilities would allow designers to develop fluid power systems in less time using the latest and most suitable components available in the market.